Pilot Position Optimization Design of WLAN System Based on Experiment - Jue Lan; Yunzhou Li; Xin Su; Shidong Zhou (Dianxin kexue)
Considering the frame structure of IEEE 802.11ac with “leading preamble plus comb-like pilot”，the performance evaluation formula of the correction scheme based on maximum likelihood estimation was derived，according to which the effect of pilot location，channel fading and subcarrier correlation was studied.Furthermore，a signalling exchange method was proposed，which ensured pilot position synchronization on both end，and a low complexity algorithm of pilot optimization according to the frequency channel amplitude information.In this way，the pilot overhead can be reduced without loss of correction performance.The experiment and simulation result shows that for ideal Rayleigh channel data，correction performance improves by 1.85 dB and 7.15 dB for unknown channel amplitude information in frequency domain and known cases respectively.For field experiment channel data，correction performance improves by 1.67 dB and 2.68 dB respectively.